2013
DOI: 10.3109/10428194.2013.802780
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated and alternative donor allogeneic stem cell transplant in patients with relapsed or refractory Hodgkin lymphoma: a systematic review

Abstract: Allogeneic stem cell transplant (allo-SCT) is considered a clinical option for patients with Hodgkin lymphoma (HL) who have experienced at least two chemosensitive relapses. The aim of this systematic review was to determine the benefits and harms of allo-SCT with an unrelated donor (UD) versus related donor (RD) allo-SCT for adult patients with HL. Alternative donor sources such as haploidentical donor cells (Haplo) and umbilical cord blood (UCB) were also included. The available evidence was limited. Ten stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…40 Our data concur with recent registry data on alternative donor use in patients with lymphoma 41 and a review by Messer et al which indicates that unrelated donor and alternative donor sources versus sibling donor allo SCT result in similar outcomes in advanced HL. 42 …”
Section: Discussionmentioning
confidence: 99%
“…40 Our data concur with recent registry data on alternative donor use in patients with lymphoma 41 and a review by Messer et al which indicates that unrelated donor and alternative donor sources versus sibling donor allo SCT result in similar outcomes in advanced HL. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported NRM incidences exceeding 50% with myeloablative conditioning allo-SCT (25)(26)(27). Reduced intensity conditionings (RIC) with different hematopoietic stem cell sources including haplo-identical family donors accomplished a reduction of early and long-term NRM of around 15-35% (8,9,22,(28)(29)(30). Nonetheless, no advantage in terms of OS and disease-free survival has been reported, in part due to an increased relapse rate of around 40-63% (4,6,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…136,138,139 Accordingly, allo-HSCT can be considered as the standard treatment option in eligible patients with sensitive relapse after auto-HSCT. 140 The value of allo-HSCT is less established in refractory HL, but may be considered in the absence of effective treatment alternatives. 141 Multiple myeloma (MM) Auto-HSCT is clearly indicated for patients less than 70 years of age who respond to first-line treatment.…”
Section: Lymphomasmentioning
confidence: 99%